Natural killer cell cytokine response to M. bovis BCG Is associated with inhibited proliferation, increased apoptosis and ultimate depletion of NKp44(+)CD56(bright) cells. - Damien Portevin; Douglas Young (PLoS ONE)
Mycobacterium bovis BCG, a live attenuated strain of M. bovis initially developed as a vaccine against tuberculosis, is also used as an adjuvant for immunotherapy of cancers and for treatment of parasitic infections. The underlying mechanisms are thought to rely on its immunomodulatory properties including the recruitment of natural killer (NK) cells. In that context, we aimed to study the impact of M. bovis BCG on NK cell functions. We looked at cytotoxicity, cytokine production, proliferation and cell survival of purified human NK cells following exposure to single live particles of mycobacteria. We found that M. bovis BCG mediates apoptosis of NK cells only in the context of IL-2 stimulation during which CD56(bright) NK cells are releasing IFN-γ in response to mycobacteria. We found that the presence of mycobacteria prevented the IL-2 induced proliferation and surface expression of NKp44 receptor by the CD56(bright) population. In summary, we observed that M. bovis BCG is modulating the functions of CD56(bright) NK cells to drive this subset to produce IFN-γ before subsequent programmed cell death. Therefore, IFN-γ production by CD56(bright) cells constitutes the main effector mechanism of NK cells that would contribute to the benefits observed for M. bovis BCG as an immunotherapeutic agent.